Price impact and the recovery of the limit order book: Why should we care about informed liquidity providers? - Dániel Havran; Kata Váradi (Hungarian Academy of Sciences, Institute of Economics, 2015)
We examine the dynamics of the limit order book recovery in the purely order-driven markets. The configuration of the current limit placements in the order book determines the costs over the mid-quote for the buy and sell trades. By analyzing the relationship between the costs of the possible trades and market order-flows, we find that bid and ask side trade costs have significant impact on the direction of future market orders. Moreover, bid and ask side trade costs revert to their characteristic state. For the further analysis of limit order placement strategies, we extend the cost of trade approach by several attributes of the entire limit order book. Using snaphots about cost of round trip indicators from Budapest Stock Exchange stocks, we decompose the shape of the immediate price impact function to main three components, slope, convexity and hump-shape. By running impluse response simulations, we document the typical temporary movements of the trade costs curves and we find empirical evidences about the "pegging to the current mid-quote" behavior of the liquidity providers.
Keywords: C32; C51; G10; G17; 330; market liquidity; resiliency; informed liquidity providers; immediate price impact function; order-driven market